Carboxy Methyl Cellulose (Cmc) As Edible Coating to Extend Shelf Life of Duku (Lansium Domesticum) During Storage - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Duku fruit (Lansium domesticum Corr.) is a tropical fruit which contains a variety of nutrients especially vitamins and minerals that are health beneficial. It has a sweet sour taste, fresh, a little seed and has a thin skin. Duku fruit contains several phytochemicals that possess high antioxidant activities. Severe pericarp browning, fruit drop, moisture loss, off-flavor and chilling injury are the predominant problems in harvested longkong fruit during handling and storage. The postharvest handling of duku fruit aims to prolong its quality and value, but it is not yet adequately developed. It is necessary to use postharvest techniques for the extension of duku shelf life. Application of carboxy methyl cellulose (CMC) as edible coating could be considered as a useful approach to maintain its product quality during preservation. Ojective of the present study focused on the effect of carboxy methyl cellulose (CMC) coating on some physicochemical, microbial and sensory characteristics of duku during preservation. Optimal results showed that weight loss, pH, total soluble solids, titratable acidity and ascorbic acid; total plate count; sensory characteristics could be maintained at appropriate levels by coating duku with 1.5% carboxy methyl cellulose (CMC). The present study attempted to investigate some of the most significant findings to extend the shelf life of duku fruit.Keywords: Duku, Carboxy methyl cellulose, Coating, Preservation, Physicochemical, Microbial, sensory